1997
DOI: 10.1002/bjs.1800840723
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of carotid surgery for acute stroke

Abstract: A definitive trial of urgent carotid surgery would need to screen large numbers of patients but could focus on patients with partial anterior circulation infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…We attempted to create a homogenous cohort of patients with presumed ICA atherosclerotic stroke because atherosclerosis is by far the most common cause of ICA occlusion. 5,14,15 However, our methodology may have resulted in ascertainment bias and some patients with atherosclerotic disease may have been missed and other patients incorrectly included. Second, the vascular imaging modality used was not uniform, because it depended on participating hospital resources and treating physician preference.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to create a homogenous cohort of patients with presumed ICA atherosclerotic stroke because atherosclerosis is by far the most common cause of ICA occlusion. 5,14,15 However, our methodology may have resulted in ascertainment bias and some patients with atherosclerotic disease may have been missed and other patients incorrectly included. Second, the vascular imaging modality used was not uniform, because it depended on participating hospital resources and treating physician preference.…”
Section: Discussionmentioning
confidence: 99%
“…13 Carotid artery atherosclerotic disease may account for up to 30% of all strokes. 16,22 Results in several clinical trials have shown a benefit for CEA over conservative medical management in preventing strokes in patients with CA stenosis. In 1991, the NASCET demonstrated a 17% absolute risk reduction for ipsilateral stroke over 2 years with endarterectomy compared with medical management in symptomatic patients with severe CA stenosis of at least 70%.…”
mentioning
confidence: 99%
“…Patients with PACI were also more likely than other categories of stroke to have a severe (>70%) carotid stenosis [8]. In a feasibility study for this trial, severe ipsilateral (70–99%) stenosis was found in 25 (20%) of 128 PACI patients [9]. Fifteen of these 40 patients were referred to in our feasibility study but were not analysed by randomised treatment.…”
Section: Introductionmentioning
confidence: 99%